(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the features of linguistic statement and semantic filling of those components of concept earth are presented, which form the binary contrasting. Eleven pair of semantic oppositions illustrate dual nature of concept, his contradiction.